Neutral technical progress and the measure of value: Along the Kaldor-Kennedy line - Up Sira Nukulkit (The University of Utah, Department of Economics, 2018)
In this paper, I investigate the question of "the effect of progress upon distribution" based on the analyses of Hicks, Robinson, Harrod, Salter, Kaldor, Samuelson, and Kennedy. The paper aims to address a neglected and controversial theoretical argument on neutral technical progress related to the measure of value that preceded and then continued to the period of the Cambridge Capital Theory Controversy. I focus on Kennedy's writings and his solutions to the complications between the measure of value and technical progress. Important intuitions behind the measure of value are crucial to the formulation of neutral technical progress in both the post-Keynesian and the neoclassical-Keynesian endogenous growth models. The paper concludes with mathematical illustrations of neutral technical progress theories.
Keywords: B22; O33; E12; 330; Neutral balanced growth; Capital controversy; Growth and distribution